KESESUAIAN TEKNIS DAN OPERASIONAL PELABUHAN PERIKANAN SAMUDERA BUNGUS DALAM MENDUKUNG PENANGKAPAN IKAN TERUKUR - Eli Nurlaela; Sandi Andika Tanjung; Eddy Sugriwa Husen (Jurnal Perikanan Unram, 2024)
This study analyzes the suitability of the technical and operational criteria of the Bungus Oceanic Fishing Port (PPS Bungus) in supporting measured fish capture. Fishing ports play a crucial role in the capture fisheries sector, providing services from fish landing to distribution and back to the sea. Based on Government Regulation Number 27 of 2021, this study evaluates the compliance of the fishing port's technical and operational criteria. The research was conducted in 2023 at PPS Bungus, West Sumatra, using a descriptive comparative method. Data were collected through observation, interviews, literature review, and documentation. The research results indicate that the port's operational criteria are not fully met, particularly in terms of fish loading and unloading activities, which only average 3-5 tons per day. Additionally, the measured fish capture policy has not been fully implemented at PPS Bungus due to the absence of post-production PNBP receipts from fishery resources. PPS Bungus needs to improve its facilities and implement the measured fish capture policy to support fisheries sustainability.